Ms - AMITO BETTY LIZ (UGANDA CHRISTIAN UNIVERSITY, 2024)
This study examined how cash management strategies affected the small-scale enterprises in Mukono Central Division's financial performance, emphasizing the value of keeping accurate records of transactions, creating cash budgeting, and controlling accounts receivable. To investigate the connection between working capital management and financial success, a cross-sectional research approach was used. The study's population consisted of 100 small-scale businesses that were registered; a sample size of 75 respondents was chosen using the sample size table developed by Krejcie and Morgan. Software from SPSS was used to examine the data that was gathered utilizing questionnaires. The results show that respondents strongly agreed on the advantages of thorough record-keeping for tax compliance, financial planning, and decision-making. Nonetheless, there are several domains where regulatory compliance and credit assessment could be strengthened by better comprehension and application. The effectiveness of cash budgeting in enhancing financial performance, particularly in controlling cash flows and reducing risks, is also widely acknowledged by small business owners. However, there is still need for improvement when it comes to using cash budgets for revenue development and financial health evaluation, as seen by the disparities in understanding and utilization. The study also emphasizes how important effective accounts receivable administration is for enhancing cash flow, preserving liquidity, and reducing the need for outside funding. It becomes clear that timely payment collection is essential for maximizing working capital, increasing profitability, and lowering default risks. The focus on precise data highlights how crucial sound accounting procedures are to making well-informed decisions. Recommendations based on the results include using computerized accounting software for financial reporting, leveraging internet-based innovations for cash management, and providing training programs to improve SME owners' and managers' financial management abilities. These interventions have the potential to enhance both the financial performance and operational sustainability of small businesses.